QUANTITATIVE ANALYSIS OF DEXTROMETHORPHAN-HBr, GUAIFENESIN, AND DIPHENHYDRAMINE-HCl IN TABLET DOSAGE FORM BY RATIO DIFFERENCE SPECTROPHOTOMETRY METHOD - TARIGAN, RIDA EVALINA; ANDRY, MUHAMMAD; ZULMI MARPAUNG, ANNISA TIFANY; NASUTION, MUHAMMAD AMIN; LUBIS, MUHAMMAD FAUZAN (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to develop a spectrophotometric method with the Ratio Difference method using ethanol pro analysis solvent to obtain the results of Dextromethorphan Hydrobromide (HBr) levels of Guaifenesin and Diphenhydramine Hydrochloride (HCl) in tablets. Methods: The Ratio Difference Sprctrophotography method involves dividing the mixture spectrum by the standard spectrum of each analyte and reducing the ratio to obtain a spectrum that does not depend on the concentration of the analyte used as a divider and can directly determine the levels of Dextromethorphan HBr, Guaifenesin, and Diphenhydramine HCl in the range 200-400 nm wavelength using experimentally calculated absorbance. Results: The maximum wavelengths of Dextromethorphan HBr, Guaifenesin, and Diphenhydramine HCl were obtained at 278 nm, 273 nm, and 252 nm, respectively. The average % accuracy obtained was 99.60% for Dextromethorphan HBr, 98.98% for Guaifenesin, and 100.32% for Diphenhydramine HCl in dosage forms. Conclusion: This method was successfully applied with simultaneous estimation to determine Dextromethorphan HBr, Guaifenesin, and Diphenhydramine HCl levels in tablet preparations and met the validation requirements.